Prevalence of methicillin-resistant Staphylococcus aureus colonization among healthcare workers at a tertiary care hospital in northeastern Brazil - Lucas S.C. da Silva; Yasmin M.F.S. Andrade; Arianne C. Oliveira; Beatriz C. Cunha; Eliana G. Oliveira; Tamara S. Cunha; Suzelle S. Mafra; Jéssica B. Almeida; Suzi P. Carvalho; Flávia S. Nascimento; Manoel Neres Santos Junior; Raiane C. Chamon; et al. (Elsevier, 2020)
Summary: Background: Staphylococcus aureus is a human pathogen of clinical importance related to a variety of infections. Aim: The objective of this study was to analyze the molecular and epidemiological characteristics of S. aureus obtained from healthcare professionals (HCP) of a hospital in southwestern Bahia, Brazil. Methods: Samples were collected from hands, nasal cavity, and laboratory coats of 80 HCP. The bacterial isolates recovered from 240 samples were identified as S. aureus, and then analyzed for their antimicrobial resistance profile, genotypic characterization, and pathogenicity. Findings: 178 isolates were identified as S. aureus, being mostly isolated from the nasal cavity. Thirty isolates (16.8%) were characterized as MRSA. The virulence gene frequency varied according to isolate source. All virulence genes were identified in at least one hand isolate. Isolates from laboratory coats did not show seb and pvl. Isolates from the nasal cavity did not exhibit pvl. The SCCmec type I was identified in 56.7% of MRSA isolates. Among MRSA isolates, 14 PFGE pulsotypes were characterized, with profile A being predominant (nine isolates). Clonal complexes CC5, CC45, and CC398 were found. MRSA isolates induced cytokine gene expression in macrophages, with IL-10 and IL-17 being expressed more often. Conclusion: We found a high colonization rate for S. aureus among HCP. Moreover, we observed that MRSA strains presented different virulence factors and could induce cytokine gene expression, indicating an urgent need to control colonization rates of HCP by MRSA isolates in order to protect hospital patients and the general public.